Snapshot retinal imaging Mueller matrix polarimeter - Wang, Yifan (Proc SPIE Int Soc Opt Eng, 2015)
Early diagnosis of glaucoma, which is a leading cause for visual impairment, is critical for successful treatment. It has been shown that Imaging polarimetry has advantages in early detection of structural changes in the retina. Here, we theoretically and experimentally present a snapshot Mueller Matrix Polarimeter fundus camera, which has the potential to record the polarization-altering characteristics of retina with a single snapshot. It is made by incorporating polarization gratings into a fundus camera design. Complete Mueller Matrix data sets can be obtained by analyzing the polarization fringes projected onto the image plane. In this paper, we describe the experimental implementation of the snapshot retinal imaging Mueller matrix polarimeter (SRIMMP), highlight issues related to calibration, and provide preliminary images acquired from the camera.